An analysis of the cognitive emphasis of high school biology final examinations in Divine Word University, Tacloban City - Carvajal, Josefina Canon 1943- ([Quezon City, 1974)
This paper determined the cognitive level and emphasis of two high school biology final examinations in Divine Word University, Tacloban City. The examination items were classified by the investigator and two biology teachers based on Bloom and others' Taxonomy of Educational Objectives: Handbook I, Cognitive Domain. The cognitive levels were tabulated and the frequencies were reported in percentages.
Thesis (M.A.T.)--University of the Philippines.
Keywords: Biology -- Study and teaching (Secondary).